AutoCAD 2000 : 3D modenling, a visual approach - Wilson, John. (Autodesk Press, 1999)
This book is about: 3D AutoCAD; Working in 3D Space; Building wireframe models; Surface models; Solid models; Paper space and 2D output; and Rendering.